The Impact of Tamil Cinema’s Popular Music on College Going Students - Catherine, HL Cordelia Angel (Journal of Advanced Research in Journalism & Mass Communication, 2022)
The study focuses on the impact of Tamil cinema popular music on people of different ages and gender with musical self-enhancement theory as its base. This research study was based on quantitative method, and the data in this study was taken in random sampling method with the use of google form. The sampling size of this study was 102 under 15 to 25 years above. Yes the study comprises identifying three dependent variables such as empathetic listening, social cohesion and pleasure through nine other independent variables which influence the dependent variables. The google form consists of a survey which obtains data from the responses in terms of these variables and conclusions are made. The results and the data obtained show that majority of the listener are empathetic, socially cohesive, and and listen to music for pleasure. How to cite this article: Catherine HLCA. The Impact of Tamil Cinema’s Popular Music on College Going Students. J Adv Res Jrnl Mass Comm 2022; 9(3): 26-30. DOI: https://doi.org/10.24321/2395.3810.202206